Internationalizing Nussbaum's model of cosmopolitan democratic education. Issue 2 (4th May 2018) - Culp, Julian
Abstract: Nussbaum's moral cosmopolitanism informs her capability-based theory of justice, which she uses in order to develop a distinctive model of cosmopolitan democratic education. I characterize Nussbaum's educational model as a 'statist model, ' however, because it regards cosmopolitan democratic education as necessary for realizing democratic arrangements at the domestic level. The socio-cultural diversity of virtually every nation, Nussbaum argues, renders it mandatory to educate citizens in a cosmopolitan fashion. Citizens must develop empathy and sympathy towards all co-citizens of their domestic polities and cope effectively with socio-cultural diversity. I criticize Nussbaum's statist model, because it neglects that due to the ways in which international institutions already constrain national decision-making, citizens will not fully enjoy the human freedom of co-determining the political choices that affect their lives unless international affairs are further democratized. Therefore I suggest extending Nussbaum's statist model and outline an 'internationalist model' of cosmopolitan democratic education.